2012
DOI: 10.1021/jo302443k
|View full text |Cite
|
Sign up to set email alerts
|

Diastereoselective One-Pot Knoevenagel Condensation/Corey–Chaykovsky Cyclopropanation

Abstract: Efforts to substitute the cyclopropane ring in a series of aryl cyclopropylnitriles led to the discovery of an operationally simple one-pot method for Knoevenagel condensation and subsequent Corey-Chaykovsky cyclopropanation giving diastereomerically pure products as a racemic mixture of enantiomers. Method development and results for variably substituted aryl acetonitriles and aldehydes in the reaction are reported. A concise synthesis of (±)-bicifadine in two steps is provided to demonstrate the utility of t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
6
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(6 citation statements)
references
References 25 publications
0
6
0
Order By: Relevance
“…In 1896, German scientist, E. Knoevenagel discovered that the condensation of aldehydes or ketones with compounds containing an active methylene group in the presence of bases, resulting in the formation of ethylene derivatives 43 , which is widely used in the organic synthesis and in the chemical˗pharmaceutical and perfume industries 55,56 . Generally, the Knoevenagel condensation were in moderate yields (30-95%) 57,58 . Here, we have found that Knoevenagel reaction of rhodanine with aldehydes (RA reaction) has very high efficiency (>98%) under mild conditions (Fig.…”
Section: Resultsmentioning
confidence: 97%
“…In 1896, German scientist, E. Knoevenagel discovered that the condensation of aldehydes or ketones with compounds containing an active methylene group in the presence of bases, resulting in the formation of ethylene derivatives 43 , which is widely used in the organic synthesis and in the chemical˗pharmaceutical and perfume industries 55,56 . Generally, the Knoevenagel condensation were in moderate yields (30-95%) 57,58 . Here, we have found that Knoevenagel reaction of rhodanine with aldehydes (RA reaction) has very high efficiency (>98%) under mild conditions (Fig.…”
Section: Resultsmentioning
confidence: 97%
“…For example, Epstein and co-workers developed a four-step synthesis of bicifadine analogues from the conjugate addition of α-bromophenylacetates with ethyl acrylate (Scheme a) . An enantioselective synthesis of 1-aryl-3-azabicyclo[3.1.0]­hexanes by nucleophilic ring opening of a chiral epoxy chloride with arylacetonitriles was accomplished by Xu and co-workers (Scheme b). , An alternative approach was developed by Micheli, which circumvents the need for constructing the pyrroldine ring system by implementation of a Corey–Chaykovsky cyclopropanation of 3-arylmaleimides (Scheme c) . In each route, the aryl vector is installed during the first step of a multistep sequence, thereby limiting the diversity of 1-aryl-3-azabicyclo[3.1.0]­hexanes that can be generated in a high-throughput fashion.…”
mentioning
confidence: 99%
“…This stereochemical outcome is commonly observed in Michael-initiated cyclopropanations. [23] To gain insight into the reaction mechanism and identify any intermediate or side products, we performed some experiments in NMR tube with the nitrile 1 b, the selenone 2 a and Cs 2 CO 3 at room temperature and monitored the samples by 1 H, 13 C, and 77 Se spectroscopy. The analysis of the mono and bidimensional NMR experiments highlighted the formation of Table 1.…”
Section: Resultsmentioning
confidence: 99%